APLIKASI PENCARIAN ORANG HILANG (PORTALANG) MENGGUNAKAN PEMINDAI WAJAH BERBASIS ANDROID: Face Recognition;TensorFlow;Artificial Intelligence. - Yudhistira Primatama; Angger Eka Rhamadani; Fathurrahman Dwi Ramtomo; Buani, Duwi Cahya Putri (JURNAL AKADEMIKA, 2021)
Artificial intelligence (AI) , is clear evidence that today's technology is very advanced, this technology can be used in any fields that require artificial intelligence. Such as medicine, tourism, industry, even government and tools that help us in our daily work. One example of Artificial Intelligence is Face Recognition which will recognize recognized faces (added). This technology will be used to help find missing people, who need facial data, which requires an Android smartphone to capture facial images through the camera, which will then be processed by TensorFlow Machine Learning which will immediately store the data. received (input). The light intensity factor, image clarity, will play an important role in the results of the Tensor Flow process, the better the light intensity, the clarity of the image, the more accurate facial recognition will be.